Sifat-Sifat Sistem Pendulum Terbalik dengan Lintasan Berbentuk Lingkaran - Resti, Nalsa Cintya (Universitas Nusantara PGRI Kediri, 2017)
The inverted pendulum is a high-order non-linear, miltivariable and highly unstable dynamic system. High-order non-linear systems in the inverted pendulum must be dilutarized to be solved easily. From the calculations that have been done can be deduced that the system from the inverted pendulum is unstable saddle system, can be controlled and can be observed. In addition the system can also be formed into a system of controlled companions and observable forms of kompanion.